Effect of welding parameters on the properties of the Ti-6Al-4V plate resistance spot weld joint. Issue 1 (March 2021) - Fatmahardi, I; Mustapha, M; Ahmad, A; Ginta, T L; Taufiqurrahman, I; Danish, M
Abstract: Titanium alloy Ti-6Al-4V properties advantage gives it a well-known reputation for decades as a reliably material used in a wide range and specific application of resistance spot welded joint such as automotive & aviation products. High strength joint is created depends on the welding parameters used in resistance spot welding. Particular problems occurred about the effect of welding parameters on pure titanium and titanium alloy mechanical and physical properties from previous researches. Some pores and acicular α' phase appeared in the microstructure, which caused partial interfacial failure mode in the tensile testing. This study is conducted to study the influence of welding parameters for Ti-6Al-4V weld nugget mechanical and physical properties and discover its optimum level of parameters. Tensile-shear testing is used to observed the optimum level. In the optimum level microstructure result reveals that in the weld nugget zone as a fusion zone the lamellar α+β is dominantly observed, this contrasts sharply with the base metal and the heat-affected zone where the primary α and β phase appear to be more dominant. The highest hardness value is discovered in the weld nugget area near the center proving the contribution of the lamellar α+β on this area.